2011
DOI: 10.1177/0020872811414597
|View full text |Cite
|
Sign up to set email alerts
|

Field education in international social work: Where we are and where we should go

Abstract: A critical review of current knowledge about international field education yielded four main conclusions. First, an unresolved debate exists relating to the meaning of international social work (ISW). Second, various motives drive students, faculty and professionals to participate in ISW. Third, developing a curriculum for ISW presents unique challenges. Fourth, four competing models of international field placement exist: (1) Independent/one-time; (2) Neighbor-country; (3) Onsite group; and (4) Exchange/recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 38 publications
1
56
0
1
Order By: Relevance
“…Reported outcomes from international social work student experiences include: personal growth; consolidated professional identity (Kreitzer et al, 2009;Nuttman-Shwartz & Berger, 2012); cultural competence/sensitivity (Gilin & Young, 2009;Krause & Broderick, 2005;Kreitzer et al, 2009;Nuttman-Shwartz & Berger, 2012); and increased understanding of the impact of poverty, oppression and human rights (Bell et al, 2015;Gilin & Young, 2009;Kreitzer et al, 2009;Larson & Allen, 2006;Saunders, Krause, & Focht, 2012;Wehbi, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported outcomes from international social work student experiences include: personal growth; consolidated professional identity (Kreitzer et al, 2009;Nuttman-Shwartz & Berger, 2012); cultural competence/sensitivity (Gilin & Young, 2009;Krause & Broderick, 2005;Kreitzer et al, 2009;Nuttman-Shwartz & Berger, 2012); and increased understanding of the impact of poverty, oppression and human rights (Bell et al, 2015;Gilin & Young, 2009;Kreitzer et al, 2009;Larson & Allen, 2006;Saunders, Krause, & Focht, 2012;Wehbi, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common strategies to incorporate international perspectives in social work curricula have included; embedding international content into existing courses, creating specific courses, and overseas study tours or international field practica (Mukherjee & Chowdhury, 2012;Nuttman-Shwartz & Berger, 2012). It is reported that one in five accredited social work schools in the USA include options for international practica in their programmes (Panos, Pettys, Cox, & Jones-Hart, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pour leur part, Rankopo et Osei-Hwedie (2011) (Heron, 2005). La préparation aux stages internationaux sous-tend aussi la reconnaissance de l'impact des identités et des expériences personnelles sur les apprentissages professionnels; en ce sens, des stagiaires LGBT ou ayant un handicap pourraient vivre des situations difficiles en raison de certaines valeurs du pays d'accueil (Mathiesen et Lager, 2007 (Nuttman-Shwartz et Berger, 2012). Epprecht (2004) mentionne de nombreux exemples où les personnes en situation d`immersion sont confrontées à des dilemmes éthiques issus d'attentes irréalistes du milieu de stage à l'égard de l'aide qu'elles peuvent apporter, d'observations de pratiques non éthiques, de lois portant atteinte à leur sécurité ou de comportements qui discriminent certaines d'entre elles.…”
Section: Des Enjeux Rencontrés Lors De Stages Internationauxunclassified
“…Social work students need to be prepared to consider the impact of the global on their local work in an increasingly globalised world (Cleak & Fox, 2011). International exchanges can play a part in preparing social work students for the complexities of intercultural local and global practice contexts (Nuttman-Schwartz & Berger, 2012). Anecdotally, there has been a marked increase in students from Australian universities travelling to countries in South Asia and South-East Asia for international field placements.…”
Section: Introductionmentioning
confidence: 99%